Recurrent Pregnancy Loss, Ayurveda - A Ray of Hope - Ashok Lamani; G. Ramadevi (AYUSHDHARA, 2023)
Motherhood is a dream of every woman. The fulfilment of this dream is a big challenge to clinicians and the couple, as many couple face problems in conception. The continuation of pregnancy after conception is also a challenge in present era. Pregnancy loss is often associated with physical, psychological and social deprivement. Couple becomes more depressive when there is recurrent pregnancy loss complicated with metabolic disorders. Here Ayurveda plays a very important role to combat with such ailments. Methods: The patient was treated with Shodhana Karma followed by oral medications for 3 months. Results: The patient conceived after 3 months of oral medication. She was under regular antenatal care and Ayurveda management throughout her gestational period. Pregnancy was uneventful till 35weeks 3days and delivered vaginally a healthy female baby of 2550grams.